IDENTIFIKASI AKTIVITAS PEREMPUAN PENJUAL IKAN DI PASAR PEUNAYONG BANDA ACEH - Ruaida - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2010)
This research is studying the working hours of women who work as fish seller at fish market Peunayong Banda Aceh. The working hours included both productive activity and daily household work (reproductive). The study also investigated the problem of raising their income and their contribution to the economy of their family. Twenty five of them were interviewed and their daily activities were directly observed in their work station. The interviews were tape-recorded and analyzed as qualitative and quantitative data. It is found that they worked in average of 16,5 hours a day, which is 12 hours for productive activity (buying selling fish) and 4,5 hours they spent for household work (reproductive activity). For widow women, their income could support 86,70% of the daily need (Rp82.800 per day) and they often were trapped in debt. The income of married women could support 70,81% of their family need, and their husbands only supported 29,19% of the needs. They also complained lack of capital, less strategic places to sell fish, low bargaining from buyer. They often feel pain in their hand and get sick due to their work condition. At home, they often lose temper if their family does not want to help them at home.  Key words:  women,  activity, and  income